ANALYSIS OF THE CALCULATION OF REBAR BEAM STRUCTURE OF FLOOR 6 ZONE 1 INDIGO BANDUNG HOTEL PROJECT USING BUILDING INFORMATION MODELING (BIM) - Parmono; Ira Nuraini; Nandan Supriatna; Dedy Suryadi (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This study aims to find out the results of calculating the requirements for rebar beam structures in the Hotel Indigo Bandung Development Project using the Building Information Modeling (BIM) method with the help of Autodesk Revit 2020 software, to be further studied against conventional methods. The type of research used in writing the review is quantitative research. The methods used in collecting data in this study are observation, interviews, and documentation studies. Data collection is used to find the truth and accuracy of the data obtained carefully and accurately so that the truth can be accounted for. The results showed that the total calculation of rebar requirements using the conventional method weighed 18843.211 kg, the total calculation of rebar requirements using the Building Information Modeling method with the help of Autodesk Revit 2020 software was 18272.58 kg, there was a difference of 570.628 kg or a difference of 3%.